2020
DOI: 10.2147/cmar.s235888
|View full text |Cite
|
Sign up to set email alerts
|

<p>Diagnostic Significance of Downregulated circMORC3 as a Molecular Biomarker of Hypopharyngeal Squamous Cell Carcinoma: A Pilot Study</p>

Abstract: Background: Circular RNAs (circRNAs) have proven to be of great clinical significance as diagnostic biomarkers in various cancers. Here, we investigate the expression of circMORC3 in hypopharyngeal squamous cell carcinoma (HSCC), exploring whether it could serve as a diagnostic marker of HSCC. Methods: CircMORC3 expression levels were detected in HSCC tissues and adjacent normal tissues using quantitative real-time polymerase chain reaction (qRT-PCR). The relationships between circMORC3 expression levels and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Eleven of these 20 circRNAs have never been reported before, and we speculated that their dysregulation might be specific for PTB. The remaining 9 circRNAs have been demonstrated to be correlated with breast cancer (hsa-SCARF1_0001), osteoarthritis (hsa-GCN1_0003), osteosarcoma (hsa-RAD54L2_002), virus infection (hsa-CREBBP_0001), ovarian cancer (hsa-FAM13B_0019), hepatocellular carcinoma (hsa-NUSAP1_0010), endometrial cancer (hsa-YY1AP1_0001), hypopharyngeal squamous cell carcinoma (hsa-MORC3_0001), and gestational diabetes mellitus (hsa-RANBP9_0002) (Fu et al, 2018;Kun-Peng et al, 2018;Hu et al, 2019;Li et al, 2019;Lou et al, 2019;Wang et al, 2019Wang et al, , 2020Guo et al, 2020;Tran et al, 2020). Interestingly, we found that all these diseases shared a common pathological ground of inflammation and immune activation with PTB, which happens to be the main way that the selected circRNAs regulate these diseases (Cappelletti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven of these 20 circRNAs have never been reported before, and we speculated that their dysregulation might be specific for PTB. The remaining 9 circRNAs have been demonstrated to be correlated with breast cancer (hsa-SCARF1_0001), osteoarthritis (hsa-GCN1_0003), osteosarcoma (hsa-RAD54L2_002), virus infection (hsa-CREBBP_0001), ovarian cancer (hsa-FAM13B_0019), hepatocellular carcinoma (hsa-NUSAP1_0010), endometrial cancer (hsa-YY1AP1_0001), hypopharyngeal squamous cell carcinoma (hsa-MORC3_0001), and gestational diabetes mellitus (hsa-RANBP9_0002) (Fu et al, 2018;Kun-Peng et al, 2018;Hu et al, 2019;Li et al, 2019;Lou et al, 2019;Wang et al, 2019Wang et al, , 2020Guo et al, 2020;Tran et al, 2020). Interestingly, we found that all these diseases shared a common pathological ground of inflammation and immune activation with PTB, which happens to be the main way that the selected circRNAs regulate these diseases (Cappelletti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 55 articles that involved details regarding 56 unique circRNAs and 5,576 HNSCC cases (all cases were reliably diagnosed via histopathological analysis) were included in this meta‐analysis. To be specific, we included 31 diagnostic studies (from 23 articles 25–47 ), 38 prognostic studies (from 38 articles 25–30,48–79 ), and 27 clinical‐pathological feature‐related studies(from 26 articles 28,29,43,47,48,50,51,53,55,56,58,63–68,70–74,76–79 ).…”
Section: Resultsmentioning
confidence: 99%
“…CircMATR3 binds to miR-188-5p and miR-448, both having a common target, USP28 . CircMORC3 downregulation in HSCC tissues and plasma samples was associated with tumor stage and tumor size (Zheng and Chen, 2020).…”
Section: Hypopharyngeal Squamous Cell Carcinoma (Hscc)mentioning
confidence: 98%